Tecnologias de informação e comunicação na educação e inclusão socio-digital: uma Avaliação do Programa de Informática na Educação – Proinfo em Fortaleza - Oliveira, Hérica Queiroz (2011)
This study aims at evaluating the National Program of Informatics in Education - PROINFO in Fortaleza, checking the impacts of this program among the subjects (students, parents, principals, teachers and managers) involved in the program. Sought, through this assessment, assess to what extent PROINFO leads to socio-digital inclusion. To perform this work, the socio-digital inclusion was considered not only as an access to a machine, but above all economical and cognitive aspects were taken into account. The methodological course of evaluation research, relevant to consider the proposed objective, consisted of three phases. In the first phase, the institutional trajectory of the program was drawn, especially in Fortaleza, through a literature review and documentary, and also by reports of managers. In the second phase, through a qualitative research, the socioeconomic profile of students was identified and how the computer is used inside and outside of school. To that end, the survey consisted initially of six public schools in elementary school, located in various suburbs, distributed in six Regional Executive Secretariats of Fortaleza (SERs). Finally, in the third phase of the research, a case study in a community school was developed, aiming at an analysis of the speech of subjects, from the following empirical categories: infrastructure of laboratories, participation of students and teachers in the lab, digital learning and socio-digital inclusion. The main results showed that the students’ digital learning occurs more out of school, in places near their houses such as lan houses and this learning does not necessarily imply, in general, in improvements in the students’ living conditions, so, it doesn’t permit, in fact, a socio-digital inclusion. Therefore, regarding to their living conditions in a structurally excluding context, the limits of PROINFO’s reach are perceived.